2011
DOI: 10.1007/s10616-011-9358-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic potential of newly synthesized furo[3,2-c]pyran-4-one derivatives in cultured human lymphocytes

Abstract: The in vitro cytotoxic potentials of Furo[3,2-c]pyran-4-one derivatives in human lymphocytes were investigated. Blood samples were obtained from six healthy donors, non-smoking volunteers, which were incubated and exposed to increasing concentrations (0.05, 0.1, 0.5, 1 and 2 mg/mL) of Furo[3,2-c] pyran-4-one derivatives which are methyl 2-methoxy-7-(4-methylbenzoyl)-6-(4-methylphenyl)-4-oxo-4H-furo [3,2-c]pyran-3-carboxylate (1a) and methyl 2-methoxy-7-(4-methoxybenzoyl)-6-(4-methoxyphenyl)-4-oxo-4H-furo[3,2-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition, LMN test was performed for the first time and revealed that TCDD exposure increased the rate of MNHEPs in hepatocytes. MN assay is a reliable test indicated chromosomal damage (Yilmaz et al 2008;Eroglu et al 2011) and MNHEPs production as 8-OH-dG is one of the key pieces of evidence for the possible involvement of antioxidant activity in oxidative DNA damage . ROS can alter vital cell components like polyunsaturated fatty acids, proteins and nucleic acids (Halliwell and Gutteridge 1990) The increased production of reactive oxygen species, lipid peroxidation, and DNA and membrane damage are always associated with TCDD exposure (Shertzer et al 1998;Hung et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LMN test was performed for the first time and revealed that TCDD exposure increased the rate of MNHEPs in hepatocytes. MN assay is a reliable test indicated chromosomal damage (Yilmaz et al 2008;Eroglu et al 2011) and MNHEPs production as 8-OH-dG is one of the key pieces of evidence for the possible involvement of antioxidant activity in oxidative DNA damage . ROS can alter vital cell components like polyunsaturated fatty acids, proteins and nucleic acids (Halliwell and Gutteridge 1990) The increased production of reactive oxygen species, lipid peroxidation, and DNA and membrane damage are always associated with TCDD exposure (Shertzer et al 1998;Hung et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significant decrease of the two parameters, namely MI and RI, which is indicative of anticarcinogenic and cytotoxic properties. [19] The data can be showed that both compounds possibly induce chromosome aberrations, particularly at high concentrations as the alkylating agent. In addition, the compounds may have contributed to MN formation by leading to centromeric division errors and dysfunction of spindle strands (stimulating aneuploidy) and forming chromosomal fractures (clastogenic).…”
Section: Scatter Diagram Between Micronucleus (Mn) Values and Concentmentioning
confidence: 99%
“…Therefore, it is very important to find out whether physical and chemical agents with the potential to have these effects have mutagenic, carcinogenic and teratogenic effects for the human genome. [19] In this study, some hybrid structured perimidine compounds were synthesized and their structures were illuminated by spectroscopic methods (Scheme 1). Genotoxic, mutagenic and carcinogenic / anticarcinogenic effects of two perimidine compounds (5 b and 5 i) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3-Acetyl-4-hydroxycoumarin (4) was prepared from 4hydroxycoumarin (3) and POCl 3 in acetic acid. [24] α,β-Unsaturated carbonyl compounds of 3-acetyl-4-hydroxycoumarin (5) were synthesized using different aryl aldehydes in the presence of piperdine as a catalyst in methanol solvent. [25] Protocol of this reaction is outlined in Scheme-2.…”
Section: Chemistrymentioning
confidence: 99%
“…They are known to possess interesting biological activities such as, phelligridimer A, a highly oxygenated and unsaturated 26membered macrocyclic metabolite with antioxidant activity [1] and phelligridin H inhibited protein tyrosin phosphatase IB and rat liver microsomal lipid peroxidation were available in fungus P. igniarius, [2] Neo-tanshinlactone isolated from S. miltiorrhiza, showed significant in vitro anti-breast cancer activity. [3] The variety of furo [3,2-c]pyrones and furo [3,2-c]coumarins have attracted the considerable attention of pharmacologist and chemist world over due to wide spectrum of remarkable biological properties e. g. antimicrobial, [4] anticancer, [5][6][7] antiinflammatory, [8] anticoagulant, [9] insect antifeedant, [10] etc. [11][12][13] Few naturally occurring and synthetic molecules possessing furo [3,2-c] Further, there is continuous effort in the development of synthetic methodology for furo [3,2-c]pyrones and furo [3,2-c] coumarins.…”
Section: Introductionmentioning
confidence: 99%